Ecotourism Development: Educational Media of Environmental Care - Hatta, Mohd.; Thamrin, Thamrin; Sudjianto, Sudjianto; Yoswati, Desi (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
One of appropriate tourism management models to be implemented while maintaining the sustainability and the beauty of the nature is sustainable tourism activities that have low impact on the environment, otherwise known as ecotourism. With the concept of ecotourism, which combines tourism with nature conservation, is believed to develop the rest of the environmental potential. Developing the natural ecotourism with alignments principles on nature and will be very beneficial to humans. Its usefulness is not only availability of a healthy environment and climate, maintaining flora and fauna that increasingly rare, but also can be a direct lecturing media, both formal and informal levels. Availability of valuable educational ecotourism area has to be monitored seriously so that the chain of intergenerational education of nature is not interrupted. Through ecotourism promoting the values of education, future generations will be more familiar with nature as an integral part of life.Â Keywords: Ecotourism, educational media, environmentCopyright Â© 2015 by Al-Talim All right reserved